2022
DOI: 10.1016/j.nurpra.2021.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A Buprenorphine Program Evaluation Before and During the COVID-19 Pandemic

Abstract: The purpose of this project was to evaluate the service delivery (i.e., attendance rate) of a buprenorphine management treatment program and compared patient recovery-related information between service methods. This is a chart review and cross-sectional comparison of pre- versus post-COVID 19 data. In the sample of 28 adults, there was no significant difference in mean attendance rates pre- (99.46%) vs. during-pandemic (96.13%) ( t =1.92, p =0.07). There was a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The majority of studies reported improved rates, although much variability was observed, potentially due to differences in data collection timepoints and the socio-demographic characteristics of target groups. For instance, some studies found retention and abstinence rates that are comparable or superior to in-person treatment rates [ 12 , 22 , 24 , 27 , 28 , 41 •]. Others reported significantly lower risk of treatment discontinuation among patients using tele-MOUD compared to those using in-person treatment [ 23 , 26 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies reported improved rates, although much variability was observed, potentially due to differences in data collection timepoints and the socio-demographic characteristics of target groups. For instance, some studies found retention and abstinence rates that are comparable or superior to in-person treatment rates [ 12 , 22 , 24 , 27 , 28 , 41 •]. Others reported significantly lower risk of treatment discontinuation among patients using tele-MOUD compared to those using in-person treatment [ 23 , 26 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates an increasing interest in tele-MOUD, especially following COVID-19. Nevertheless, limitations in the reviewed literature were identified, including the uncontrolled, retrospective, and cross-sectional design of many studies [ 8 , 12 ], the inability to generalize findings due to their single setting design, the narrow specialty of care they cover, or the small population size among others [ 10 , 12 , 24 – 26 , 28 , 30 , 43 – 45 ], potentially missing data and short-term follow-up [ 8 , 12 , 28 , 31 , 42 – 44 ], and the potential for selection bias [ 10 , 44 ]. Finally, the majority of the studies included in this review focused on the clinician experiences, with only few studies reporting on patient experiences through direct patient interviews [ 10 ].…”
Section: Limitations and Identified Gapsmentioning
confidence: 99%